MONETARY ASPECTS OF UKRAINE’S INTEGRATION INTO THE EUROPEAN UNION - Sharov, Oleksandr (Journal of European Economy, 2018)
Issues of Ukraine’s integration into the EIJ finance and banking sector are considered. The author’s suggestions are based on the fact that Ukraine is still on the early stage of integration. Therefore, now we can discuss only the main problems and the variants how to settle them. Meanwhile, they are divided into: a) the problems of central banks immediately arousing because of entering the EU (in most cases these are procedure requirements), and b) the problems related to improvement of national finance and banking system, its adjustment to that of West European. The latter ones are of crucial importance, therefore the government of Ukraine should settle them notwithstanding the plans and schedules of the EU enlargement, since it is a prerequisite for the national needs of Ukraine’s economy.